Pengembangan Media Edukasi Interaktif Bertema Lokal Konten Indonesia di SDN Sekarpuro, Pakis, Kab. Malang: Penelitian - Jevon Jeremy; Safitri Aprillia Putri; Dian Pratiwi Willyarti; Neng Lanny Jauhari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Sekarpuro Elementary School faces the challenge of a lack of varied and engaging learning media, as well as the suboptimal utilization of literacy facilities such as the library and school bulletin board. Through a visual communication design approach and the active participation of teachers and students, the implementation team will design and implement various interactive media, such as illustrated local storybooks, educational game cards, and interactive thematic bulletin boards. These media are expected to increase students' interest in learning, material absorption, and foster a love of local culture. This community service activity aims to develop interactive educational media with local Indonesian content to support students' learning process. Through collaboration between the academic world and elementary schools, this program is expected to make a real contribution to strengthening literacy and learning innovation in the elementary education environment.